Virgin bark tapping of some RRIC 100 series clones - Samaranayake, C.; Waidyanatha, U.P. De S.; Pathiratne, L.S.S.; De Soysa, A.G.A. (Rubber Research Institute. Agalawatta, 1987)
All RRIC 100 series clones reached tappability much earlier than the two control clones viz. RRIM 600 and PB 86. Significantly higher yield per tree per tapping was obtained in the first year on a 1/2 S d/3 system compared to 1/2S d/2 tappings in many of the clones tested. However, during the second year there was no significant differences in yields obtained on both frequencies indicating that the tree was able to replenish the latex removed in a tapping, much faster than in the first year of tapping. The data presented indicate the possibility of tapping all recommended clones on 1/2S d/32 system of tapping from the second year, without any adverse effects.
Keywords: Agriculture; Rubber; Tapping systems; Yield